Nutrition through the life cycle - Brown, Judith E.; Isaacs, Janet S.; Krinke, U. Beate; Lechtenberg, Ellen; Murtaugh, Maureen A.; Sharbaugh, Carolyn; Splett, Patricia L.; Stang, Jamie; Wooldridge, Nancy H. (Cengage Learning, 2014)
Explains the nutritional foundations necessary for the growth, development, and normal functioning of individuals in each stage of the life span. This book brings clarity to key concepts as well as addresses new research on the roles played by healthful diets, nutrients, gene variants, and nutrient-gene interactions